Two-stage collaborative information interaction reliability improvement for the distribution grid - Shi, Zhan (Frontiers in Energy Research, 2024)
The impulse noise generated by large volume of power electronics devices imposes hazardous impact on information interaction reliability in low-voltage distribution grid. Impulse noise suppression requires a comprehensive consideration of collaboration between transmission and reception sides, which has not been thoroughly addressed by existing literatures. In this paper, we propose a two-stage collaborative information interaction reliability improvement algorithm to minimize the bit error rate (BER) of information interaction under the impulse noise. In the first stage, the transmission-side peak-to-average power ratio (PAPR) is reduced based on adaptive particle swarm optimization (PSO) enabled partial transmit sequence (PTS). In the second stage, reception-side dual signal blanking is proposed based on transmission-side PAPR and reception-side useful signal power estimation and peak median ratio. The transmission-reception collaborative information interaction reliability improvement is realized through two aspects. First, transmission-side PAPR reduction improves the performance of reception-side signal blanking by making it easier to distinguish useful signal from impulse noise. Second, transmission-side PAPR is utilized to improve estimate accuracy of both coarse threshold and precise threshold in dual signal blanking. Simulation results show that the proposed algorithm outperforms existing algorithms in both PAPR reduction and BER performances to achieve information interaction reliability improvement effectively.